2021
DOI: 10.3390/math9212640
|View full text |Cite
|
Sign up to set email alerts
|

An Optimal Weighted Combined Model Coupled with Feature Reconstruction and Deep Learning for Multivariate Stock Index Forecasting

Abstract: Stock index prediction plays an important role in the creation of better investment strategies. However, prediction can be difficult due to the random fluctuation of financial time series. In pursuit of improved stock index prediction, a hybrid prediction model is proposed in this paper, which contains two-step data pretreatment, double prediction models, and smart optimization. In the data pretreatment stage, in order to carry more information about the prediction target, multidimensional explanatory variable… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…Zhu [22] found that the VMD-BIGRU model outperformed GRUs and LSTM in predicting high returns when constructing a comprehensive financial investment decision system. Wang [23] tested a combination optimization model using BiLSTM and BIGRUs for simultaneous prediction on four stock groups, demonstrating superior performance compared to other benchmark models. Taguchi [24] simulated stock investments in a proposed portfolio strategy, and found that BIGRU had the lowest error, although its generalizability varied for different datasets and given tasks.…”
Section: Bigrumentioning
confidence: 99%
See 1 more Smart Citation
“…Zhu [22] found that the VMD-BIGRU model outperformed GRUs and LSTM in predicting high returns when constructing a comprehensive financial investment decision system. Wang [23] tested a combination optimization model using BiLSTM and BIGRUs for simultaneous prediction on four stock groups, demonstrating superior performance compared to other benchmark models. Taguchi [24] simulated stock investments in a proposed portfolio strategy, and found that BIGRU had the lowest error, although its generalizability varied for different datasets and given tasks.…”
Section: Bigrumentioning
confidence: 99%
“…where X is the current solution position vector, X* is the current optimal solution position vector, t is the current number of iterations, and A and C are the coefficient vectors. The vectors A and C are given by Equations ( 22) and (23).…”
Section: − →mentioning
confidence: 99%